Early defoliation in a temperate warm and semi‐arid Tempranillo vineyard: vine performance and grape composition. (29th October 2013) - Risco, D.; Pérez, D.; Yeves, A.; Castel, J.R.; Intrigliolo, D.S.
Abstract Background and Aims Early defoliation (ED) can reduce vine yield and improve fruit composition in vigorous vineyards. The objective of this study was to test the effectiveness of this technique for the Vitis vinifera (L.) cultivar Tempranillo under the temperate warm and semi‐arid climatic conditions of south‐eastern Spain. Methods and Results Four treatments were applied over three seasons to drip‐irrigated vines, planted with rows orientated north–south and shoots vertically positioned. Non‐defoliated vines (control) were compared with vines defoliated either just before anthesis (phenological stage H, treatment ED) or at fruitset [phenological stage J, treatment late defoliation (LD)]. In the fourth treatment, only the leaves facing east were removed at phenological stage H (treatment east ED). In the fourth experimental season, all treatments were managed similarly. Defoliation did not reduce fruitset but reduced berry mass, particularly in the ED and the LD treatments. Defoliation, however, had a cumulative negative effect on vine bud fertility. Even in the fourth experimental season, the yield of the ED treatment was 18% lower than that of the control. Both the ED and particularly the LD treatments increased berry total soluble solids (TSS) and phenolic concentration. The effect of leaf removal on berry TSS and phenolic concentration was not significant in the east ED treatment. Conclusions Defoliation at fruitset was the most effective treatment for increasing berry phenolics and TSS while maintaining must acidity. Growers should take into account, however, the important yield penalty because of defoliation, particularly in the mid‐term. Significance of the Study Early defoliation of Tempranillo grapes growing in semi‐arid and temperate climates needs to be applied with caution and probably limited to specific seasons while consecutive defoliations should be avoided.